1978
DOI: 10.1097/00000658-197802000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Critical Operative Management of Small Bowel Obstruction

Abstract: The records of 238 patients with the diagnosis of small bowel obstruction at the University of Illinois Hospital from 1967 through the spring of 1976 were reviewed. Mortality, intra-operative management, and clinical findings were evaluated. Previous reports list a mortality of gangrenous small bowel obstruction, secondary to hernia and/or adhesions, as greater than 20%, although in this series, the mortality was 4.5% in patients with gangrenous small bowel obstruction. The present data reveal a 60% incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(62 citation statements)
references
References 15 publications
2
58
0
2
Order By: Relevance
“…Although preoperative diagnosis of intussusception is difficult due to the atypical and non-specific presentation in adults and it is generally determined at laparotomy, it may also be diagnosed by CT, especially in colo-colonic types caused by tumor lesions (17)(18)(19). It has been reported that CT is the most sensitive diagnostic test for the confirmation of intussusception with a diagnostic accuracy of 58%-100% (5,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although preoperative diagnosis of intussusception is difficult due to the atypical and non-specific presentation in adults and it is generally determined at laparotomy, it may also be diagnosed by CT, especially in colo-colonic types caused by tumor lesions (17)(18)(19). It has been reported that CT is the most sensitive diagnostic test for the confirmation of intussusception with a diagnostic accuracy of 58%-100% (5,20).…”
Section: Discussionmentioning
confidence: 99%
“…Cecum (arrowhead) to splenic flexure (arrow) high rate of malignant causes, although the necessity and extent of the resection in each patient has been controversial (18). Intraoperative reduction has also often been discouraged for the fear of causing tumor rupture and potentially upstaging the cancer (8,17,22).…”
Section: Discussionmentioning
confidence: 99%
“…5 Stewardson et al emphasized a classic quartet of findings such as leucocytosis, fever, tachycardia and localized tenderness. 10 Plain radiographs may be normal or suggest bowel obstruction, but it is difficult to differentiate between SBV and other causes of obstruction that may resolve with conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…4 The main indications of surgery for intestinal obstruction are severe abdominal pain, dehydration, circulatory abnormalities of the digestive tract, and failure of conservative treatment to alleviate symptoms. 5,6 Kyphosis is a condition in which the posterior convex curvature of the spinal column is abnormally increased in the sagittal plane. 7,8 Although kyphosis often accompanies spinal caries, cases of degenerative age-related lumbar kyphosis and kyphotic changes due to osteoporotic spinal compression fractures have also been observed.…”
Section: Discussionmentioning
confidence: 99%